Surface Engineering of Nanocellulose-Based Composites for Smart Slow-Release Fertilizers: A Short Review - Agus Wedi Pratama; Aminatun Nisa; Muh. Misbah Muhtadi; Ach. Fauzan Mas’udi; Sri Rejeki; Adin Novitasari; Nur Andita Prasetyo; Mohd Nor Faiz Norrrahim (Department of Chemistry, FMIPA, UNEJ, 2025)
The global agricultural sector faces a critical paradox: the necessity of increasing food production to support a growing population versus the severe environmental degradation caused by the inefficiency of conventional nitrogen, phosphorus, and potassium (NPK) fertilizers. Conventional fertilizers exhibit nutrient use efficiencies (NUE) often below 50%, leading to substantial economic losses and ecological crises such as eutrophication and greenhouse gas emissions. Slow-release fertilizers (SRFs) offer a viable solution, yet current commercial technologies rely heavily on non-biodegradable synthetic polymers that contribute to soil microplastic accumulation. Nanocellulose, encompassing cellulose nanocrystals (CNC), cellulose nanofibrils (CNF), and bacterial nanocellulose (BNC), has emerged as a premier bio-based candidate for next-generation SRF matrices due to its high aspect ratio, mechanical robustness, and abundant reactive surface hydroxyl groups. However, the intrinsic hydrophilicity of native nanocellulose poses a significant challenge in retarding nutrient release in aqueous environments. This review critically examines the role of surface engineering—specifically oxidation, esterification, graft copolymerization, and cross-linking—in modulating the release kinetics of nanocellulose-based fertilizers. We analyze the transition from simple diffusion-controlled mechanisms to complex swelling and erosion-controlled architectures enabled by surface functionalization. Furthermore, we evaluate the environmental implications of these materials through the lens of Life Cycle Assessment (LCA), highlighting the potential of agricultural waste-derived nanocellulose to close the loop in a circular bioeconomy. The synthesis of recent data suggests that precise tuning of surface chemistry can increase nutrient retention times from hours to months, positioning functionalized nanocellulose as a cornerstone of sustainable precision agriculture.